Cytological abnormalities and the accuracy of citology as the screening method in HIV seropositive Aids/women - Fialho, Susana C.A.V.; Almeida Filho, Gutemberg L.; Passos, Mauro R.L.; maldonado, Paula M.; Val, Isabel C. do; Andrade, Ângela C.V. de (Brazilian Journal of Sexually Transmitted Diseases, 2002)
Background; the number of HIV infected women has increased and the immunosupression due to HIV infection has been changing HPV’s natural history. High- risk (HR4IPV) are considered the main agent in inducing the development of CIN. Therefore, HIV seropositive women have a high incidence of CIN. Pap smear is used as the screening method in the detection of such lesions. Objective: to analyse the accuracy of Pap smear as the screening method in HIV seroposilivc/Aids women. Method: descriptive transversal study in 130 HIV infected/ Aids women The clinical aspects observed in the lower genital tract have been analysed through Pap smear, colposcopy and directed biopsy. Results: Pap smear and the histopatology showed mild agreement. Pap smear sensibility and especificily in the detection of HPV and CIN were 0.78 and 0.57. respectively. Conclusion: the Pap smear should be used as a screening method in HIV seropositive women.